Assessing the Probability of Megathrust Earthquakes in Indonesia: A Review of Seismic Hazard Assessment and Mitigation Strategies - Heinrich Rakuasa; Yamres Pakniany (Journal of Loomingulisus ja Innovatsioon, 2024)
This research addresses the probability of megathrust earthquakes occurring in Indonesia, which is an earthquake-prone region due to its position on the Pacific Ring of Fire. The background of this research emphasizes the importance of seismic hazard assessment to understand the likelihood and impact of such seismic events. The method used is a literature study, by analyzing various sources of information, including scientific journals and government reports, to evaluate mitigation strategies that have been implemented. The results and discussion show that while Indonesia has made progress in early warning systems and seismic hazard maps, challenges in risk communication and public awareness still need to be addressed. The conclusions of this study emphasize the need for improved mitigation strategies and disaster preparedness to reduce the risks associated with future large earthquakes and tsunamis.